2005
DOI: 10.1074/jbc.m406934200
|View full text |Cite
|
Sign up to set email alerts
|

Type I PDZ Ligands Are Sufficient to Promote Rapid Recycling of G Protein-coupled Receptors Independent of Binding to N-Ethylmaleimide-sensitive Factor

Abstract: Molecular sorting of G protein-coupled receptors (GPCRs) between divergent recycling and lysosomal pathways determines the functional consequences of agonist-induced endocytosis. The carboxyl-terminal cytoplasmic domain of the ␤ 2 adrenergic receptor (␤ 2 AR) mediates both PDZ binding to Na ؉ /H ؉ exchanger regulatory factor/ezrin/radixin/moesin-binding phosphoprotein of 50 kDa (NHERF/EBP50) family proteins and non-PDZ binding to the N-ethylmaleimide-sensitive factor (NSF). We have investigated whether PDZ int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
76
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 57 publications
2
76
0
Order By: Relevance
“…Mutation of the novel sorting sequence produced a dramatically different phenotype (default recycling) than mutation of a previously defined recycling signal present in the distal ␤ 2 ADR C-tail, which greatly inhibits recycling when mutated (5)(6)(7)15). This suggests an epistatic relationship between these distinct sorting sequences, in which the acidic dileucine sequence functions upstream of both Hrs-and the PDZ-dependent recycling sequence, mediating the initial sorting of endocytosed receptors to the specialized recycling mechanism (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mutation of the novel sorting sequence produced a dramatically different phenotype (default recycling) than mutation of a previously defined recycling signal present in the distal ␤ 2 ADR C-tail, which greatly inhibits recycling when mutated (5)(6)(7)15). This suggests an epistatic relationship between these distinct sorting sequences, in which the acidic dileucine sequence functions upstream of both Hrs-and the PDZ-dependent recycling sequence, mediating the initial sorting of endocytosed receptors to the specialized recycling mechanism (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…studies defined a minimal recycling signal, contained within the distal 4 -10 residues of the ␤ 2 ADR C-terminal tail (C-tail), which is necessary for efficient recycling of the ␤ 2 ADR and sufficient to re-route a distinct GPCR from lysosomal to recycling pathways (5)(6)(7)15). We recently showed that a sequence corresponding to residues 366 -413 of the ␤ 2 ADR C-tail, which includes these distal residues, is sufficient to confer Hrs-dependent recycling when fused to a truncated mutant V2 vasopressin receptor (V2R 362T) that otherwise recycles by default and in an Hrs-independent manner (16,20,24).…”
Section: The C-terminal Pdz Ligand Present In the ␤ 2 Adr Cytoplasmicmentioning
confidence: 99%
See 2 more Smart Citations
“…In that case, NHERF-1 is thought to act by tethering surface AM 2 receptors to the actin cytoskeleton in a manner also seen with epidermal growth factor receptors (42). By contrast, NHERF-1 promotes the agonist-mediated recycling of ␤ 2 -ARs, which also have a PDZ motif (SLL) (30). The mechanism by which NHERF-1 exerts these differing effects on different GPCRs remains unknown.…”
Section: Discussionmentioning
confidence: 99%